Broad Severe Acute Respiratory Syndrome Coronavirus 2 Cell Tropism and Immunopathology in Lung Tissues From Fatal Coronavirus Disease 2019. (10th April 2021) - Ramos da Silva, Suzane; Ju, Enguo; Meng, Wen; Paniz Mondolfi, Alberto E; Dacic, Sanja; Green, Anthony; Bryce, Clare; Grimes, Zachary; Fowkes, Mary; Sordillo, Emilia M; Cordon-Cardo, Carlos; Guo, Haitao; et al.
Abstract: Background: Coronavirus disease 2019 (COVID-19) patients manifest with pulmonary symptoms reflected by diffuse alveolar damage (DAD), excessive inflammation, and thromboembolism. The mechanisms mediating these processes remain unclear. Methods: We performed multicolor staining for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) proteins and lineage markers to define viral tropism and lung pathobiology in 5 autopsy cases. Results: Lung parenchyma showed severe DAD with thromboemboli. Viral infection was found in an extensive range of cells including pneumocyte type II, ciliated, goblet, club-like, and endothelial cells. More than 90% of infiltrating immune cells were positive for viral proteins including macrophages, monocytes, neutrophils, natural killer (NK) cells, B cells, and T cells. Most but not all infected cells were angiotensin-converting enzyme 2 (ACE2) positive. The numbers of infected and ACE2-positive cells are associated with extensive tissue damage. Infected tissues exhibited high levels of inflammatory cells including macrophages, monocytes, neutrophils, and NK cells, and low levels of B cells but abundant T cells consisting of mainly T helper cells, few cytotoxic T cells, and no regulatory T cells. Robust interleukin-6 expression was present in most cells, with or without infection. Conclusions: In fatal COVID-19 lungs, there are broad SARS-CoV-2 cell tropisms, extensive infiltrated innate immune cells, and activation and depletion of adaptive immune cells, contributing to severe tissue damage, thromboemboli, excess inflammation, and compromised immune responses. Abstract : We provide an atlas of lung immunopathology of fatal severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infections, revealing unexpected broad cell tropism and infection of parenchymal, endothelial, and immune cells by SARS-CoV-2, which are associated with massive tissue damage and thromboemboli.